Pengaruh Persepsi Mahasiswa Akuntansi, Motivasi Diri, Pertimbangan Pasar Kerja, dan Perhargaan Finansial Terhadap Minat Berkarir Sebagai Akuntan Publik - Emme Oktaviani Sinulingga; Astuti Yuli Setyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the perception of accounting students, self-motivation, job market considerations, and financial rewards on career interests as public accountants. This study is a quantitative study with a sample of accounting students. The sample of this study was 130 accounting students. The data source used is primary data. The data collection technique used in this study was through the distribution of questionnaires. Testing in this study was carried out by validity testing and reliability testing. The classical assumption test includes normality testing, heteroscedasticity testing, and multicollinearity testing. The data analysis technique used multiple linear regression analysis. The test results showed that accounting students' perceptions, self-motivation, job market considerations, and financial rewards had a positive and significant effect on career interests as public accountants.